Prevalence and associated factors of bacterial vaginosis among pregnant women in Hue, Vietnam - Anh TC Nguyen; Na TL Nguyen; Trang TQ Tran; Tuyen T Nguyen; Thu TA Hoang; Linh M Tran; Khoi Tuan Tran; Thanh DC Phan; Xuan T Nguyen; Tam M Le; An V Le; Andres Salumets; et al. (Journal of Infection in Developing Countries)
Introduction: Bacterial vaginosis (BV) is the most frequent vaginal infection affecting women of childbearing age worldwide. It is associated with significant adverse healthcare outcomes, especially during pregnancy. Although screening for BV could reduce potential pregnancy-related obstetric complications, there is no routine screening of pregnant women for BV in Vietnam. We aimed to identify the prevalence of BV among pregnant women and the associated factors in two tertiary hospitals in Hue, Vietnam.